Níveis de nitrogênio na produtividade e qualidade de grãos de trigo - Brunetto, Diego Junior (2016)
Wheat is the main winter crop option in southern Brazil. Widely cultivated, domestic production is not sufficient to meet domestic demand, making the country a major importer of this cereal. The lack of an internal policy to encourage the cultivation of wheat, associated with production risks hamper the further expansion of culture in the South. The increase in income through adoption of management practices such as increased levels of nitrogen can optimize the cultivation of maize in the south of the country. In this context, this work, which was developed in a farm in the municipality of Dois Vizinhos, Paraná, aimed to evaluate the productivity and quality of wheat grain intake of different levels of nitrogen (0, 40, 80, 120 and 160 kg of N ha-1) cover. The plant height and yield components number of ears per square meter, ear length; number of spikelets per spike; number of grains per ear, thousand grain weight and hectoliter weight responded linearly to higher nitrogen levels. The wheat yields adjusted to a quadratic equation as a function of nitrogen levels.